Developing a sustainable solution for recycling electric arc furnace dust via organic acid leaching. (1st August 2018) - Halli, Petteri; Hamuyuni, Joseph; Leikola, Maria; Lundström, Mari
Graphical abstract: Highlights: A new green method for recycling of EAF dust is proposed. Selective dissolution of Zn and Pb from EAF dust investigated using organic acid. Alkaline roasting decomposes insoluble zinc ferrite to a leachable zincate. Abstract: The current study demonstrates and proposes a new method for sustainable treatment of electric arc furnace (EAF) dust. The raw material is one of the largest and fast growing hazardous waste fractions produced. Globally, annual EAF production of steel generates more than 12 M tonnes of dust today. The dust is rich in Fe but also contains toxic and volatile metals. The main components in the dust include Fe, Mn, Zn, Pb, and Cr. However, Zn and Pb in the dust inhibits its recycling back to the steel process. The novel process approach employs alkaline roasting with NaOH at 450 °C, followed by organic acid leaching using 0.8 M citric acid at 40 °C under oxygen purging, for two hours. Zinc ferrite (ZnFe2 O4 ), which is the main Zn carrier in the EAF dust is highly refractory making selective Zn vs. Fe leaching impracticable. Roasting was observed to transform EAF dust ZnFe2 O4 mineralogy into favourable form of sodium zincate (Na2 ZnO2 ) and sodium ferrate (NaFeO2 ), the former being an easily leachable Zn compound and the latter keeping Fe in solids. Under the optimized conditions, selective leaching of 100% of Zn vs. Fe (<10%) could be conducted, in addition ≥80% of Pb could be leached. Consequently, Fe and Zn rich recyclable secondary fractions were produced from hazardous EAF dust, both fractions being suitable raw materials for primary metal production.